The betrayal of Anne Frank : [large type] a cold case investigation - Sullivan, Rosemary, 1947- (Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
Using a new technology, recently discovered documents, and sophisticated investigative techniques, a retired FBI agent and a cold case team painstakingly pieced together the months leading to the infamous arrest of Anne Frank and her family--and came to a shocking conclusion.